Exploring the potential of biomass-derived carbons for the separation of fluorinated gases with high global warming potential - Sosa, Julio E. (2024)
Funding Information: The single-component adsorption isotherms of R-32, R-125, R-134a, SF6 and N2 on the four biomass-derived porous carbons were measured by gravimetry in an ISOSORP high-pressure magnetic-suspension balance (MSB, Rubotherm GmbH, Germany). Approximately 0.30\u20130.40 g of the solid porous materials were loaded into the adsorption cells and then degasified at 373.15 K for 9 h under vacuum. After degassing, the sample was put into contact with the gas at a given pressure and temperature until the recorded mass stabilized. An adsorption point is under thermodynamic equilibrium when there are no discernible changes in weight, pressure, and temperature. This process is repeated continuously until the maximum pressure is reached. Finally, depressurization is performed to measure desorption points and check that the desorption branch of the isotherm coincides with the adsorption branch. The process is completed when the difference between the initial weight and the weight of the material after degassing is equal to zero. The adsorption equilibrium data are reported as excess adsorption, qex [28,30]; the corresponding values of total adsorption, q, determined from the experimental are reported in Tables S1\u2013S3 in the Supporting Information, SI. Finally, the adsorption-desorption equilibrium data were fitted using the isothermal dual-site Langmuir (DSL) model [ 54\u201356]. The parameters of the DSL model are shown in Tables S4 and S5 of SI.The authors acknowledge the financial support from the European Union's Horizon Europe research and innovation programme under grant agreement No 101082048\u2013- the MAR2PROTECT project. This work was also financed by national funds from FCT/MCTES (Portugal) through CEECIND/004431/2022 (I.M.), and the Norma Transitória DL 57/2016 Program Contract (R.P.P.L.R. and M.B.). Publisher Copyright: © 2024 The Authors